Public–private tragedy: Stigma, victimization and community identity. Issue 2 (May 2018) - O'Leary, Nicola
On 13 March 1996, Thomas Hamilton shot and killed 16 children and 1 teacher at Dunblane Primary School, Scotland. In the weeks and months that followed, intense and extensive media coverage focused on the victims, the community, the aftermath and the subsequent intense and emotional outpouring of grief for Dunblane that seemed to come from around the world. The impact of crime on indirect victims has generated a wealth of research; however, surprisingly little is known regarding the impact of 'high-profile' crime on a community living in a location that has become synonymous with the crime that took place there. Drawing on a unique set of interviews with members of the Dunblane community, this article explores the victimizing experiences and processes by which some build their sense of identity in the wake of such a high-profile crime. Empirical findings highlight the ways in which private tragedy becomes public property and how some community members are stigmatized by, manage (and are sometimes resilient to) the impact of wider societal reaction. The aftermath of events at Dunblane encouraged some to identify as victims, whilst others were more resilient to the stigmatizing effects of the crime that labelled them and their community with a 'spoiled victim identity'.